(untitled) (Ukrainian Journal of Ophthalmology, 2024)
Background: Given a rising tendency in the rate of ocular trauma, there is an increasing need in surgeries for orbital, ocular adnexal and periorbital reconstruction. The susceptibility to resorption is a common drawback of the biological tissues used as a plastic material in contemporary orbital surgery. Non-biological hollow porous polyvinyl formal (PVF) hydrogel implants capable of integration with adjacent biological tissues offer a new opportunity for reconstructive surgery. Purpose: To examine the in vivo and in vitro biocompatibility of a synthetic PVF-based hydrogel implant material. Material and Methods: Scanning electron microscopy (SEM) analysis; in vitro evaluation of the biocompatibility of the PVF hydrogel implant material in terms of its cytotoxicity, genotoxicity and effects on marker enzymatic activities of L929 fibroblasts; and in vitro study on implant incorporation. Results: A cross-linked polyvinyl formal hydrogel for orbital endoprosthesis surgery was synthesized. Our in vitro cytotoxicity and genotoxicity tests of the hydrogel and tests of its effects on marker enzymatic activities of L929 fibroblasts demonstrated safety. All hydrogel implant samples, after being sealed into polypropylene bags and autoclaved for 15 min at 121 °C and 1.04 atm steam pressure, were found to be sterile. In all rats in which the hybrid hydrogel implant was placed subcutaneously in the back, there was prompt relief of edema at the site of postoperative suture. The inflammatory reactions seen in the tissues adjacent to the implant included mostly mild diffuse lymphocytic infiltration close to the implant surface, with no inflammatory reactions seen at the sites more remote from the implant. Conclusion: Our in vivo and in vitro study of the PVF hydrogel demonstrated its high biocompatibility in terms of its cytotoxicity, genotoxicity and effects on marker enzymatic activities of fibroblast cells, with no post-implantation complications, but a step-by-step improvement in the relationship between the implant and adjacent tissues. The findings of this study allow us to recommend the developed PVF hydrogel for further research on the potential for using it as an implant for filling postoperative cavities and endoprosthesis in orbital and periorbital reconstruction.